Day-ahead economic dispatch of wind-integrated microgrids using coordinated energy storage and hybrid demand response strategies - Qinglin Meng; Ying He; Sheharyar Hussain; Jinghang Lu; Josep M. Guerrero (Scientific Reports)
Abstract This study proposes an optimized day-ahead economic dispatch framework for wind-integrated microgrids, combining energy storage systems with a hybrid demand response (DR) strategy to address real-time grid pricing dynamics. The model evaluates five operational scenarios: (1) conventional dispatch without renewable/storage/DR integration, (2) wind power participation, (3) coordinated wind-storage operation, (4) wind-DR synergy, and (5) full integration of wind, storage, and DR. A two-stage demand response mechanism is developed, integrating incentive-based load adjustments with price elasticity modeling through a tariff scaling factor approach. The analysis compares operational costs, renewable energy utilization efficiency, load profile characteristics, and user comfort levels across all scenarios. Results demonstrate that the combined deployment of wind generation, battery storage, and adaptive DR significantly reduces microgrid operating costs while enhancing peak load management. The integrated strategy proves most effective in balancing supply-demand dynamics, improving grid stability through synergistic storage-DR coordination, and maintaining user satisfaction. Case studies validate the framework’s practicality in achieving cost-efficient dispatch decisions without compromising renewable energy integration capabilities. The proposed model achieves a 23.4% reduction in operational cost and over 88% utilization of renewable energy, with load peaks significantly flattened and user comfort exceeding 90% throughout the scheduling horizon.